ANALYSIS OF THE PROSPECTIVE USE OF SAN MARKO INTERIOR DECORATIVE MATERIALS - OLIJNYK, Halina (Herald of Khmelnytskyi National University. Technical sciences, 2022)
SAN MARKO decorative materials appeared on the domestic market relatively recently. The Italian brand of decorative materials is represented by a variety of paint and varnish products for interior solutions. It is difficult for the modern consumer to understand the choice of SAN MARKO decorative materials, as there is not enough information regarding the specifics of the use of these products. SAN MARKO decorative materials offer unique innovative solutions with high-quality characteristics, focused on each individual client, following current market trends in the field of interior and design. With the help of SAN MARKO decorative materials, you can create interior styles, exquisite decors, thereby not neglecting any of the client’s wishes. The products of the Italian brand are not just the widest color palette, they represent unlimited possibilities for creative ideas. Decorative coatings and effects created by these materials fascinate with their originality and rich artistic content. The secret of the success of the SAN MARKO line of decorative materials lies in the fact that they offer not only unique, radically new solutions, but also maintain high quality characteristics, as well as the fact that each customer with completely different requests in terms of aesthetics and technology will find something for himself optimal material for creating an interior. The Italian art of interior design conquered the international market, became a model of sophistication and taste, which is perceived as a globally recognized example of style. SAN MARKO decorative materials carry an important mission – they pass on to today’s generation a rich heritage in which unsurpassed Italian craftsmanship techniques reproduce the age-old traditions of the southern people, updated with the help of modern materials and techniques. SAN MARKO decorative materials are presented in a wide range of species and a rich palette of colors. This is a great modern tool for those who value creativity, sophistication, and quality. Creating a unique decor using materials from an Italian manufacturer is not just work, but the creativity of designers, master interior decorators and other professionals working with paint and varnish materials.